2010
DOI: 10.1111/j.1365-2230.2009.03427.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of metronidazole 1% cream and pimecrolimus 1% cream in the treatment of patients with papulopustular rosacea: a randomized open-label clinical trial

Abstract: Pimecrolimus cream is no more efficacious than metronidazole cream in the treatment of PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
0
37
0
4
Order By: Relevance
“…Another randomized, open‐label clinical trial over twelve weeks comparing pimecrolimus 1 % cream and metronidazole 1 % cream showed similar responses .…”
Section: Off‐label Topical Therapiesmentioning
confidence: 84%
“…Another randomized, open‐label clinical trial over twelve weeks comparing pimecrolimus 1 % cream and metronidazole 1 % cream showed similar responses .…”
Section: Off‐label Topical Therapiesmentioning
confidence: 84%
“…Koca et al . (2010) compared the effectiveness of 1% pimecrolimus to metronidazole on 48 patients in an open-labeled, randomized, single-center study and found them equally effective [45]. Prospective randomized, multi-center studies have not yet been performed.…”
Section: Treatment Of Rosaceamentioning
confidence: 99%
“…Pimecrolimus has been shown to be a safe, effective therapeutic alternative to topical corticosteroids and its indications are now being extended 7 . Conflicting data regarding the effectiveness of topical pimecrolimus on rosacea have been published 8–13 . In this study, we aimed to investigate the efficacy and safety of 1% pimecrolimus cream in patients with mild to moderate rosacea.…”
Section: Introductionmentioning
confidence: 99%